1994
DOI: 10.1161/01.hyp.23.5.587
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor regulates cardiac hypertrophy and transforming growth factor-beta 1 expression.

Abstract: The role of angiotensin II via the angiotensin type 1 or type 2 receptor in the development of cardiac hypertrophy was determined in adult male Sprague-Dawley rats subjected to coarctation of the abdominal aorta. Five groups of animals were studied: coarctation, coarctation plus DuP 753, coarctation plus PD 123319, sham plus DuP 753, or sham operation. Type 1 receptor blockade was accomplished with DuP 753 given in the drinking water and type 2 blockade with PD 123319 delivered by osmotic minipumps beginning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(98 citation statements)
references
References 38 publications
2
93
1
2
Order By: Relevance
“…7,32 Previous studies have provided compelling evidence that Ang II induces fibrosis in the heart and kidneys primarily through the TGF␤ 1 pathway. 3,17,19 Therefore, the marked up-regulation of cardiac and renal CTGF mRNA and protein expression found in dTGR is likely to be mediated through TGF␤ 1 . The close co-localization of CTGF gene expression with Col I and Col III mRNA expressions supports this notion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,32 Previous studies have provided compelling evidence that Ang II induces fibrosis in the heart and kidneys primarily through the TGF␤ 1 pathway. 3,17,19 Therefore, the marked up-regulation of cardiac and renal CTGF mRNA and protein expression found in dTGR is likely to be mediated through TGF␤ 1 . The close co-localization of CTGF gene expression with Col I and Col III mRNA expressions supports this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II may also regulate collagen degradation by attenuating matrix metalloproteinase activities, and by enhancing the production of TIMP-1. [17][18][19][20] We investigated CTGF in transgenic rats harboring human renin and angiotensinogen genes (dTGR). We then examined whether or not calcineurin-dependent pathways participate in regulating CTGF gene expression.…”
mentioning
confidence: 99%
“…It has been shown that selective stimulation of 34,35 There is evidence that these actions are under inhibitory control by angiotensin AT 2 receptors. 36 Indeed, angiotensin AT 2 receptor antagonizes both pressor and growth effects of the angiotensin AT 1 receptor 37,38 and the central mediated angiotensin-induced release of vasopressin and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…68 -70 Activation of the renin-angiotensin system is an important inducer of tissue hypertrophy and interstitial fibrosis, with angiotensin II acting as a potent growth factor in the myocardium. 68,[71][72][73][74] Although development of LVH is an adaptive response that reduces LV wall stress in the face of elevated arterial pressure, it is also an ominous prognostic sign that predicts a high rate of cardiovascular events. The difference between physiological LVH secondary to physical training and pathological LVH from hypertension is the difference between intermittent load and continuous overload on the heart.…”
Section: Pathophysiologymentioning
confidence: 99%